An exposition of constructivism account to construct knowledge and to create meaningful learning environment for teacher education - Abd Rahman, Fadzilah; Ab. Jalil, Habibah; Hassan, Aminuddin (Minda Masagi Press, 2008)
Since last ten years, it becomes indispensable to talk about constructivism in relation to the teaching and learning process. Yet the term of constructivism is still not well defined and contradicts. Generally constructivism refers to a set of views about how individuals learn and about how those who help them to learn ought to facilitate, which in this paper referred as Constructivist Learning Account (CLA). CLA holds an assumption that learners actively construct their own sets of meanings and understandings; knowledge is not a mere copy of the external world, nor is knowledge acquired by passive absorption or by simple transference from one person (educator) to another (a learner or knower). Clearly, knowledge is constructed not acquired. CLA also stresses that we cannot be certain that any two individuals will construct the same understandings. Even if they use the same linguistic formulations to express what they have learned, their deep understandings might be quite different. Hence, a better understanding of constructive learning accounts as a component of a long life learning process and how teacher education programme should engage with it is needed to create a meaningful learning environment.